Staff training in positive behaviour support for behaviour that challenges in people with intellectual disability: cost-utility analysis of a cluster randomised controlled trial. Issue 2 (March 2020) - Hunter, Rachael Maree; Vickerstaff, Victoria; Poppe, Michaela; Strydom, Andre; King, Michael; Hall, Ian; Crabtree, Jason; Omar, Rumana; Cooper, Vivien; Biswas, Asit; Hassiotis, Angela
Abstract : Background: Behaviour that challenges in people with intellectual disability is associated with higher healthcare, social care and societal costs. Although behavioural therapies are widely used, there is limited evidence regarding the cost and quality-adjusted life-years (QALYs). Aims: We aimed to assess the incremental cost per QALY gained of therapist training in positive behaviour support (PBS) and treatment as usual (TAU) compared with TAU using data from a cluster randomised controlled trial (Clinical Trials.gov registration: NCT01680276). Method: We conducted a cost-utility analysis (cost per QALY gained) of 23 teams randomised to PBS or TAU, with a total of 246 participants followed up over 36 months. The primary analysis was from a healthcare cost perspective with a secondary analysis from a societal cost perspective. Results: Over 36 months the intervention resulted in an additional 0.175 QALYs (discounted and adjusted 95% CI −0.068 to 0.418). The total cost of training in and delivery of PBS is £1598 per participant plus an additional cost of healthcare of £399 (discounted and adjusted 95% CI −603 to 1724). From a healthcare cost perspective there is an 85% probability that the intervention is cost-effective compared with TAU at a £30 000 willingness to pay for a QALY threshold. Conclusions: There was a high probability that training in PBS is cost-effective as the cost of training and delivery of PBS is balanced out by modest improvements in quality of life. However, staff training in PBS is not supported given we found no evidence for clinical effectiveness.